"We get double slammed!": Healthcare experiences of perceived discrimination among low-income African-American women. (August 2020) - Okoro, Olihe N; Hillman, Lisa A; Cernasev, Alina
Background: On account of their racial/ethnic minority status, class, and gender, African-American women of low socioeconomic status are among the least privileged, underserved, and most marginalized groups in the United States. Generally, African Americans continue to experience poorer health outcomes, in which disparities have been attributed to socioeconomic inequities and structural racism. This objective of this study was to explore the lived experiences of low-income African-American women in interacting with the healthcare system and healthcare providers. Methods: Twenty-two in-depth one-on-one interviews were conducted with low-income African-American women. The audio-recorded interviews were transcribed verbatim. An inductive content analysis was performed, using an analytical software, Dedoose ® to enabled hierarchical coding. Codes were grouped into categories which were further analyzed for similarities that led to the emergence of themes. Results: A key finding was the experience of discriminatory treatment. The three themes that emerged relevant to this category were (1) perceived discrimination based on race/ethnicity, (2) perceived discrimination based on socioeconomic status, and (3) stereotypical assumptions such as drug-seeking and having sexually transmitted diseases. Conclusion and Recommendations: Low-income African-American women experience less than satisfactory patient care, where participants attribute to their experience of being stereotyped and their perception of discrimination in the healthcare system and from providers. Patients' experiences within the healthcare system have implications for their healthcare-seeking behaviors and treatment outcomes. Healthcare personnel and providers need to be more aware of the potential for implicit bias toward this population. Healthcare workforce training on culturally responsive patient care approaches and more community engagement will help providers better understand the context of patients from this population and more effectively meet their healthcare needs.